2005
DOI: 10.1109/tit.2004.840897
|View full text |Cite
|
Sign up to set email alerts
|

On the capacity of MIMO broadcast channels with partial side information

Abstract: Abstract-In multiple-antenna broadcast channels, unlike point-to-point multiple-antenna channels, the multiuser capacity depends heavily on whether the transmitter knows the channel coefficients to each user. For instance, in a Gaussian broadcast channel with transmit antennas and single-antenna users, the sum rate capacity scales like log log for large if perfect channel state information (CSI) is available at the transmitter, yet only logarithmically with if it is not. In systems with large , obtaining full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
1,019
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,169 publications
(1,043 citation statements)
references
References 20 publications
18
1,019
1
5
Order By: Relevance
“…Therefore, the individual average sum rate capacity [11][12][13] can be obtained by averaging (11) with respect to p γSINR m (γ) as C m = ∞ 0 log 2 (1 + γ) p γSINR m (γ)dγ. By adding the individual average sum rate capacities of the K s scheduled users, we can obtain the total average sum rate capacity as …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the individual average sum rate capacity [11][12][13] can be obtained by averaging (11) with respect to p γSINR m (γ) as C m = ∞ 0 log 2 (1 + γ) p γSINR m (γ)dγ. By adding the individual average sum rate capacities of the K s scheduled users, we can obtain the total average sum rate capacity as …”
Section: Discussionmentioning
confidence: 99%
“…Some work has been done in extending the opportunistic beamforming idea to the case where base station and mobile stations all have multiple antennas [9], but this has not been yet studied extensively. Multiple random beams are used in [64] with limited feedback to communicate with many users. Further work on feedback reduction has been conducted in [65], where it is shown that the feedback rate can be minimized without losing the gains due to adaptive modulation and multi-user diversity.…”
Section: Schedulingmentioning
confidence: 99%
“…The idea is based on transmitting M random beams and exploiting multi-user diversity. The details are described in [18] (a similar construction, albeit with little analysis, appears in the appendix of [38]). …”
Section: B Opportunistic Random Beamformingmentioning
confidence: 99%
“…In this way, the multi-user diversity of the system can be exploited. (This is the jist of the idea-for more details see [18]. )…”
Section: Basically During Any Coherence Interval the Transmitter Chomentioning
confidence: 99%